Istota posługi głoszenia Słowa Bożego w świetle "Mów" św. Leona Wielkiego - Dąbrówka, Michał (Vox Patrum, 2014)
St. Leo the Great’s theological view is characterized by a deep sense of the liturgy as an actualization of the saving mystery of Christ. This belief has its resemblance in tasks which are performed by pope’s Sermons. They are – first of all – uncovering this mystery’s presence in “here and now” of the liturgical celebration, leading into its essence, and indicating in which way this celebration can be prolonged in everyday live by the believers. In this way sermons help them in deeper participation in the Holy Mass and extracting life-giving strength from the mystery which is celebrated. Therefore the preaching ministry is regarded by St. Leo as a grave responsibility, from which a priest who presides over the liturgy should not dispense with. Considering a sermon as a part of the liturgy Pope regards it as an instrument of God’s grace, and a space to praise the God for what He has made in the history of salvation.